Eagle Head Element - Paula Wesley (1976- ) (2010)
Two eagle head designs, facing opposite directions, in black and red acrylic paint. Good condition. FDSNCA Graduate 2012. Located at FDSNCA. Copyright held by artist. Photograph by Highlight Studio.